Leitura cultural no ensino de literatura - Jesus, Jairton Mendonça de (2011)
This work brings a reflection about as the cultural questions may permeate the teaching of literature. Traditionally the teaching of literature gives directions for the study of literary historiography which, by times, it does not elect as a priority the reading of literary text. Thus, our main purpose is to think the social formation of reader over in the way we will search new way-outs for the literature classes as to the questionings purposed by the cultural criticism. By the vies of Cultural Studies, this methodological reflection comes out from the beginning that the identity belonging and the ideological questions are fundamental to the literature classes, then, in the reading and in the discussion on literary text, we may include racial and sexual and gender questions. Collected data at Itabaiana s schools serve us from empirical base to question the traditional historiographic teaching. As to these reflections, the purpose is to suggest that the literary text is taken as an indispensable means in the teaching of literature. Methodologically, this work embodies in questions about identity, cultural studies and racial questions to approach the representation of Negro in literature. We exploited the reflections of Tzvetan Todorov and Regina Zilberman about identity and culture. Therefore, the literary reading is defended as a practice of interaction between cultural inheritance and current critical view. For us to apply a purpose of literary text reading, we chosen a few Jorge de Lima s texts in order to comment on a purpose of cultural reading which assesses the reader s active role when questioning different approaches about the representation of Negro in literature.